2021
DOI: 10.35513/21658005.2021.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and diversity of macroinvertebrates of the Bouhamdane Stream (northeast of Algeria)

Abstract: Freshwaters are among the most threatened ecosystems, particularly in North Africa where urbanization and climate change are exerting an important pressure on aquatic fauna. Long-term investigation of macroinvertebrates is one of the best ways of tracking and understanding the influence of environmental and anthropogenic pressures on community dynamics. In this study, we focus on determining the community structure and diversity of benthic macroinvertebrates as well as the state of aquatic physicochemical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…The observed results are similar with other similar descriptions for Algerian rivers, where was found important differences in environmental parameters and community parameters in function of human intervention of surrounding basins (Reggam et al, 2015;Sellam et al, 2017Sellam et al, , 2019Baaloudj et al, 2020). Nevertheless, the results obtained in the present study that revealed the marked importance of amphipods would agree with results of Rouibi et al (2021) who described the marked abundance of crustaceans in Bouhamdane river in Algeria. It is a similar situation in comparison to Algerian rivers in Boumerzoug (East of Algeria) where it was found marked absence of Plecoptera in spite of high-water quality (Bekhouche et al, 2017).…”
Section: Tablesupporting
confidence: 93%
“…The observed results are similar with other similar descriptions for Algerian rivers, where was found important differences in environmental parameters and community parameters in function of human intervention of surrounding basins (Reggam et al, 2015;Sellam et al, 2017Sellam et al, , 2019Baaloudj et al, 2020). Nevertheless, the results obtained in the present study that revealed the marked importance of amphipods would agree with results of Rouibi et al (2021) who described the marked abundance of crustaceans in Bouhamdane river in Algeria. It is a similar situation in comparison to Algerian rivers in Boumerzoug (East of Algeria) where it was found marked absence of Plecoptera in spite of high-water quality (Bekhouche et al, 2017).…”
Section: Tablesupporting
confidence: 93%
“…Spatial (inter-site) variability in the richness of taxonomic orders was detected. Our results reveal that the majority of macroinvertebrates in the studied environments are similar to those in the temporary superficial studied habitats in Morocco (Giudicelli, Thiéry, 1998), Italy (Bazzanti et al,1996(Bazzanti et al, , 2009Bagella et al, 2010), Spain (Boix et al, 2004(Boix et al, , 2008(Boix et al, , 2009, and in Algeria (Lounaci et al, 2000;Khelifa, 2019;Khelifa et al, 2016;Meziane et al, 2020, 2022Rouibi et al, 2021). A total of 29 taxa and 1715 individuals were collected during this study.…”
Section: Study Of the Underground Fauna Of Wellssupporting
confidence: 71%
“…By comparison, groundwater populations are much less diversified compared to watercourses, in particular, those of watercourses in Kabylie Djurdjura (Lounaci, 2005), Wadi Djedir and Wadi M'zi (Sellam et al, 2017), Oued Boumerzoug (Bekhouche et al, 2017), watershed of the Soummam (Zouggaghe, 2020), Oued Sybousse (Baaloudj et al, 2020(Baaloudj et al, , 2022, and Wadi Bouhamdane (Rouibi et al, 2021). Figure 6 represents the spatial distribution of taxonomic richness, which revealed variation from one well to another.…”
Section: Study Of the Underground Fauna Of Wellsmentioning
confidence: 99%
“…Despite all that, the study of macroinvertebrates in the streams of Algeria has only been undertaken in recent decades in order to put an inventory as exhaustive as possible and to have knowledge of their systematics, their ecology, and their biogeography (Rouibi et al, 2021). The reports for Algerian rivers mentioned marked heterogeneity at spatial scale along river course and the differences of the kinds of water bodies in term of community structure, specifically in species diversity and dominant species (Rouibi et al, 2021;Ferguani and Arab, 2013), that would be explained also due marked geographical isolation and environmental heterogeneity (Bekhouche et al, 2017;Ferguani and Arab, 2013;Rouibi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite all that, the study of macroinvertebrates in the streams of Algeria has only been undertaken in recent decades in order to put an inventory as exhaustive as possible and to have knowledge of their systematics, their ecology, and their biogeography (Rouibi et al, 2021). The reports for Algerian rivers mentioned marked heterogeneity at spatial scale along river course and the differences of the kinds of water bodies in term of community structure, specifically in species diversity and dominant species (Rouibi et al, 2021;Ferguani and Arab, 2013), that would be explained also due marked geographical isolation and environmental heterogeneity (Bekhouche et al, 2017;Ferguani and Arab, 2013;Rouibi et al, 2021). Sampling protocol: To assess and monitor changes in the physicochemical and biological quality of freshwater, we sampled the macroinvertebrates and nine physicochemical parameters (depth of water body, water speed, conductivity, dissolved oxygen [O 2 ], pH, nitrate, nitrite, salinity, and water temperature) in each site monthly from October 2020 to September 2021.…”
Section: Introductionmentioning
confidence: 99%